Psychological Contract, Self-Efficacy, Job Stress, and Turnover Intention: A View of Job Demand-Control-Support Model - Shao, Lijin; Guo, Hui; Yue, Xiaoyao; Zhang, Zhaohua (Frontiers in Psychology, 2022)
The outbreak of COVID-19 has caused enterprises to face more challenges, including operational management, production and sales management, and human resource management and other issues. In the context of the global knowledge economy, employees with high knowledge and skills have become an important source of corporate growth and breakthroughs. However, employees may have the intention to transfer to other companies due to the pressure of external and internal environment, so it will be the main topic to explore the change of employees' turnover intention. The purpose of this study was to explore the influence mechanism that propels employees’ self-efficacy, job stress and turnover intention and the moderating effect of transformational leadership. A total of 553 valid responses from several information service companies in China are used in the data analysis. The results of the path analysis with structural equation modeling show that employees psychological contract has a positive effect on self-efficacy and a negative effect on job stress; employees self-efficacy has negative effects on job stress and turnover intention; transformational leadership plays a significant moderator in the research framework. Based on research findings, the theoretical and managerial implications are presented.